(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Reforms aimed at educating young people in the spirit of patriotism, respect for our national traditions and values, raising a spiritually mature and physically healthy harmonious generation, protecting their rights and interests are creating the basis for the cultivation of ambitious specialist personnel who are able to take responsibility for the future of our country, mobilize all their potential for Initiative, for the At the same time, the need arises for the study, measurement, systematization and constant proofreading of qualimetric analysis of the patriotic level of students. In measures to educate young people spiritually, morally and physically harmoniously, tasks such as "raising selfless and patriotic young people with a high spirituality, a strict life position, a broad outlook" are set.